PENGARUH KEPUASAN, KEPERCAYAAN DAN HARGA TERHADAP LOYALITAS WISATAWAN PENGGUNA LAYANAN BOOKING.COM - Lisa Wulandari, Ni Luh; Kusuma Negara, I Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 2 (2016): Jurnal IPTA (December 2016)DO - 10.24843/IPTA.2016.v04.i02.p18)
Online Travel Agent is popular sites as travel planner for tourist. Online Travel Agent provides ease on choosing accommodation or other tour facility for tourist. Booking.com is the biggest online travel agent at this time which giving service on reserving hotel room. Booking.com becomes popular among the tourist and very interested especially for reserved hotel room due to Booking.com provide additional facility which given for customer who loyal using service this online travel agent. Therefore, the purpose of this study is to know The Effect of Satisfaction, Trust and Price on Tourist Loyalty who uses Service of Booking.com. Sample on this research is 100 respondents with using quota sampling technique directed to tourist who ever using service of Booking.com more than 1 time and classified as Secret Deal and Genius Booker Customer. Collecting Data technique are observation non participation, questionnaire with likert scale, literature study and online survey. By hypothesis test with t test and F test, the result are (1) Satisfaction has influence positive and significant on Loyalty of Tourist. (2) Trust has influence positive and significant on Loyalty of Tourist (3) Price has influence positive and significant on Loyalty of Tourist.(4) Satisfaction, Trust and Price has influence positive and significant on Loyalty of Tourist as simultaneous. Through coefficient determination test Satisfaction, Trust and Price variable able to explain Loyalty 70,60%. Linier Regression Analyze state that independent variable has positive coefficient value 2,593, 2,303 and 4,988 with result Price as independent variable which very dominant influence Loyalty of Tourist for using service online travel agent Booking.com.
Keywords: Online Travel Agent, Satisfaction, Trust, Price, Loyalty